2023
DOI: 10.1111/tpj.16205
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal transcriptomics and metabolic profiling provide insights into gene regulatory networks during lentil seed development

Abstract: SUMMARY Lentil (Lens culinaris Medik.) is a nutritious legume with seeds rich in protein, minerals and an array of diverse specialized metabolites. The formation of a seed requires regulation and tight coordination of developmental programs to form the embryo, endosperm and seed coat compartments, which determines the structure and composition of mature seed and thus its end‐use quality. Understanding the molecular and cellular events and metabolic processes of seed development is essential for improving lenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…The pattern of the P influence, though, is not consistent among the P treatments, which may suggest the existence of additional factors regulating the expression of F3H. Yu et al reported that two genes in the FLS family, FLS1 and FLS2, are highly expressed in the early stages of seed development, while another gene in the FLS family, FLS3, is highly expressed in the later stages of seed development, suggesting that the FLS genes may play different roles in regulating seed development [30]. In the study conducted by Jia et al in tobacco leaves, it was observed that in higher P treatment there was a reduction in the transcript levels of NtCHS (chalcone synthase), NtCHI (chalcone isomerase), NtF3H (flavanone 3-hydroxylase), NtF30H (flavanone 30-hydroxylase) and NtFLS (flavonol synthase), while NtFLS transcript levels were increased in both juvenile and mature leaves in the lower P treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of the P influence, though, is not consistent among the P treatments, which may suggest the existence of additional factors regulating the expression of F3H. Yu et al reported that two genes in the FLS family, FLS1 and FLS2, are highly expressed in the early stages of seed development, while another gene in the FLS family, FLS3, is highly expressed in the later stages of seed development, suggesting that the FLS genes may play different roles in regulating seed development [30]. In the study conducted by Jia et al in tobacco leaves, it was observed that in higher P treatment there was a reduction in the transcript levels of NtCHS (chalcone synthase), NtCHI (chalcone isomerase), NtF3H (flavanone 3-hydroxylase), NtF30H (flavanone 30-hydroxylase) and NtFLS (flavonol synthase), while NtFLS transcript levels were increased in both juvenile and mature leaves in the lower P treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the control of seed size in lentils operates through the regulation of cell division, involving both cell expansion and the overall seed growth [29]. In a recent transcriptomic analysis of lentil embryos, seed coats and whole seeds, specific genes and co-expressed gene sets were found to be prevalent in distinct tissues and developmental stages, distinguishing the expression patterns of the embryo from those of the seed coat [30].The availability of the current lentil's genome assemblies that include the cultivated lentil (Lens culinaris) and the wild relative (Lens ervoides) has facilitated the potential to gain knowledge regarding mechanisms regulating even complex traits [22].…”
Section: Introductionmentioning
confidence: 96%
“…Lentils ( Lens culinaris ) have nutritional, economical, and environmental advantages as an excellent source of protein-based human diet ( Kumar et al., 2016 ). Lentils have twice the level of proteins than cereals and are rich in minerals, polyphenols, and vitamins ( Yu et al., 2023 ). Lentil proteins have been a source of novel food formulations in milk substitute, curd-like products, meat products, extruded products, and baked goods ( Boye et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge is to identify and utilize the advantageous traits in a breeding program ( Gur and Zamir, 2004 ). Molecular tools for lentil breeding such as genome sequencing and transcriptome profiling are being developed rapidly ( Fedoruk et al., 2013 ; Haile et al., 2020 ; Song et al., 2022 ; Yu et al., 2023 ), which have rendered this relatively facile for identifying the target genes. In this study, we identified the LTP gene that encodes Len c3 in lentil and performed genetic screening via gene sequencing for LTP mutation from a collection of natural lentil accessions.…”
Section: Introductionmentioning
confidence: 99%